Diabetes mellitus (DM) and periodontal disease: a preliminary study among medical staff from 3 public primary care clinics in Kuantan, Malaysia - Tin, Myo Han; Md Aris, Mohd Aznan; Osman, Iskandar Firzada; S., Sorayah; I., Razida; Yaacob, Munirah; Abdullah, Fa’iza; Saub, Roslan; Than, TS; T., Mahendran; H., Padmini (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association, 2015)
Evidences of bilateral relationship between diabetes mellitus (DM) and Periodontal disease (PD) have been increasing and published in oral health practices since 20th century. Nevertheless, awareness of medical staff on relationship between DM and PD and screening PD using self-reported questionnaires has still been limited. This study was done to assess DM and PD status of medical staff and their perception on DM and PD relationship and screening PD using self-reported questionnaires at health clinics.